2019
DOI: 10.1007/s00005-019-00534-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fucoidan, a Potential New, Natural, Anti-Neoplastic Agent on Uterine Sarcomas and Carcinosarcoma Cell Lines: ENITEC Collaborative Study

Abstract: The aim of the study was to assess the activity of fucoidan on the uterine sarcomas (MES-SA and ESS-1) and carcinosarcoma cell lines (SK-UT-1 and SK-UT-1B) and its toxicity on the human skin fibroblasts (HSF). Two uterine sarcomas and two carcinosarcoma cell lines were examined, as a control HSF were used. Cell viability was assessed with MTT test, apoptosis with caspase-3 activity and cell cycle by assessment of DNA synthesis. Fucoidan significantly decreases cell viability in SK-UT-1, SK-UT-1B, and ESS-1 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
(24 reference statements)
2
13
0
Order By: Relevance
“…They concluded that fucoidan "enhances the anti-cancer activity" of tested cytostatic drugs. Furthermore, they observed the induction of apoptosis and cell cycle arrest among cells treated with fucoidan what corresponds with our previous findings [9,33].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…They concluded that fucoidan "enhances the anti-cancer activity" of tested cytostatic drugs. Furthermore, they observed the induction of apoptosis and cell cycle arrest among cells treated with fucoidan what corresponds with our previous findings [9,33].…”
Section: Discussionsupporting
confidence: 89%
“…Labeled cells were analyzed by flow cytometer FACSCalibur (Becton Dickinson, Franklin Lakes, NJ, USA), operating with CellQuest software (BD Biosciences, San Jose, CA, USA) to quantitatively assess the caspase-3 activity. The methodology of apoptosis assessment were described in detail elsewhere [9].…”
Section: Assessment Of Apoptosismentioning
confidence: 99%
See 3 more Smart Citations